Young farmers club together for climate resilience [Zambia] - Bafana, Busani (Technical Centre for Agricultural and Rural Cooperation, 2018)
Development efforts look to harness youth as the driving force for a new generation of climate-smart farmers, as adverse climate change impacts wreak ever greater havoc on agriculture across ACP countries.